Normative Approach to Resolving Jurisprudential Debate on the Legal Nature of the Constitutional Court - Beladjouz, Wissame (Journal of Human Sciences, 2025)
The legal nature of the Constitutional Court has been the subject of much debate in academic circles, both at conferences and in scholarly articles, particularly since the adoption of the constitutional amendment of 2020, which established the Constitutional Court as a constitutional institution to replace the Constitutional Council. In this paper, we will examine the legal nature of the Constitutional Court and classify it as a special judicial body. To justify this classification, we will conduct research and provide evidence, both tangible and intangible, that confirms and establishes both the judicial character and the special nature of the Constitutional Court